Persepsi Siswa Terhadap Penerapan Model Pembelajaran Inkuiri Melalui Grup WhatsApp Pada Mata Pelajaran Bahasa Arab - Hadi Saputra; Munawarah; Hamidah; Nurul Wahdah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2022)
Discourses regarding the application of the inquiry learning model have been widely carried out and indicate that the application of this model has the potential to increase student independence. However, there is still little research directed at the application of social media-based inquiry learning models in learning Arabic. Therefore, this study aims to describe students' perceptions regarding the application of this learning model to learning Arabic through WhatsApp groups in madrasas. Descriptive quantitative research with a survey type was used in this case, as well as data analysis using a formula to get the percentage of student perceptions. The results of this study reported that as many as 49.6% of students chose structured inquiry strategy statements and as many as 50.4% of students chose free inquiry strategies. This study recommends the application of inquiry learning models through other social media in Arabic subjects.